A biomimetic approach towards a universal slippery liquid infused surface coating - Ryan A. Faase; Madeleine H. Hummel; AnneMarie V. Hasbrook; Andrew P. Carpenter; Joe E. Baio (Beilstein Journal of Nanotechnology)
One biomimetic approach to surface passivation involves a series of surface coatings based on the slick surfaces of carnivorous pitcher plants (Nepenthes), termed slippery liquid-infused porous surfaces (SLIPS). This study introduces a simplified method to produce SLIPS using a polydopamine (PDA) anchor layer, inspired by mussel adhesion. SLIPS layers were formed on cyclic olefin copolymer, silicon, and stainless steel substrates, by first growing a PDA film on each substrate. This was followed by a hydrophobic liquid anchor layer created by functionalizing the PDA film with a fluorinated thiol. Finally, perfluorodecalin was applied to the surface immediately prior to use. These biomimetic surface functionalization steps were confirmed by several complimentary surface analysis techniques. The wettability of each surface was probed with water contact angle measurements, while the chemical composition of the layer was determined by X-ray photoelectron spectroscopy. Finally, ordering of specific chemical groups within our PDA SLIPS layer was determined via sum frequency generation spectroscopy. The hemocompatibility of our new PDA-based SLIPS coating was then evaluated by tracking FXII activation, fibrin generation time, clot morphology, and platelet adhesion to the surface. This hemocompatibility work suggests that PDA SLIPS coatings slow or prevent clotting, but the observation of both FXII activation and the presence of adherent and activated platelets at the PDA SLIPS samples imply that this formulation of a SLIPS coating is not completely omniphobic.